Priorytety programowe kandydatów na urząd prezydenta Ukrainy w 2019 roku: Program Priorities of Candidates for the Office of President of Ukraine in 2019 - Pietnoczka, Paweł (Przegląd Wschodnioeuropejski, 2019)
The aim of the article is to present the proposals of candidates running for the office of President of Ukraine in 2019. It has been shown what issues they paid closest attention to in their election programmes, how they intended to ensure national security, restore territorial integrity, fight corruption, and improve the socio-economic and political situation in Ukraine. Attention was brought to the proposals of those candidates who received at least 10% support in the election. Therefore, the election programmes of Volodymyr Zelensky, Petro Poroshenko, Yulia Tymoshenko and Yuriy Boyko were analysed